A cat scratch disease case presenting with underarm painful lymphadenopathy - Yardimci, Bulent (Asian Journal of Medical Sciences, 2022)
Cat Scratch Disease is an infectious disease that typically begins as a cutaneous lesion and causes proximal regional lymph nodes enlargement. In general, it is infected as a result of cat saliva and scratches. It rarely causes systemic manifestations. Since it may be observed worldwide, the differential diagnosis should be strictly introduced in case of local lymphadenopathies.